2020
DOI: 10.1111/jcpt.13174
|View full text |Cite
|
Sign up to set email alerts
|

General characteristics, economic burden, causative drugs and medical errors associated with medical damage litigation involving severe cutaneous adverse drug reactions in China

Abstract: What is known and objective To investigate the general characteristics, economic burden, causative drugs and medical errors associated with litigation involving severe cutaneous adverse drug reactions (SCADRs) in China, with the aims of improving rational medication use and reducing the extent of damage from SCADRs. Methods This study analysed 150 lawsuit judgements involving SCADRs from 2005 to 2019, collected from China Judgments Online. Results and discussion In total, 50% of lawsuits stemmed from SCADRs oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
3
1
Order By: Relevance
“…The medical institution was responsible for 90% of the liability for compensation and reserves the right of patients to follow-up litigation. This result is similar to findings in our previous studies on severe cutaneous ADRs [ 21 ]. Disability often leads to higher compensation levels, which may be related to the increased indirect costs caused by patient disability.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The medical institution was responsible for 90% of the liability for compensation and reserves the right of patients to follow-up litigation. This result is similar to findings in our previous studies on severe cutaneous ADRs [ 21 ]. Disability often leads to higher compensation levels, which may be related to the increased indirect costs caused by patient disability.…”
Section: Discussionsupporting
confidence: 93%
“…We found that 41.03% of the cases proceeded to the second or retrial and execution process, which is significantly lower than our previous research on severe cutaneous ADRs (55%) [21], which may be more acceptable to patients given the results of verdicts awarding payments for damages caused by NADs compared to the damage caused by severe cutaneous ADRs. However, medical service providers should still pay attention to the rational use of NADs.…”
Section: Characteristics Of Litigation Cases Of Nad-related Mmldscontrasting
confidence: 72%
See 2 more Smart Citations
“…Moreover, no study explores the relationship between self-perceived medical errors and emergency medicine physicians’ distress. Most of the existing studies in China are from the patients’ perspective, and focus on medical incidents/disputes which had a more serious impact on patient safety 11 12. Some studies investigated patients’ perceptions and attitudes towards doctors after medical errors 13.…”
Section: Introductionmentioning
confidence: 99%